Penataan Penjualan Ikan Asin Bebas Formalin sebagai Makanan Khas Masyarakat Kendari menuju Produk Unggulan Sehat dan Higienis - Darmayani, Satya -; Hasna, Nur (Universitas Negeri Padang, 2021)
Community services are focused on getting healthy and hygienic food sold in the city of Kendari. In the initial stage, the examination is carried out by taking samples of salted fish sold in traditional and modern markets and then tested whether they contain formaldehyde. If the findings of salted fish contain formaldehyde, education and guidance will be given about alternative formalin ingredients that are safe for health. A total of 60 samples of salted fish were taken from 7 traditional markets in Kendari city and 2 modern markets. The formalin content of fish was analyzed qualitatively. The results of this analysis showed 6 samples or about 10% contained formaldehyde. Based on the results of the analysis of 60 samples, it was found positive results in traditional markets and negative results for samples from modern markets. Thus, the Kendari City Traditional Market has stated that salted fish contains formaldehyde and is very dangerous if consumed continuously.